Mouse Models of Sjögren’s Syndrome with Ocular Surface Disease - Masli, Sharmila (Int J Mol Sci, 2020)
Sjögren’s syndrome (SS) is a systemic rheumatic disease that predominantly affects salivary and lacrimal glands resulting in oral and ocular dryness, respectively, referred to as sicca symptoms. The clinical presentation of ocular dryness includes keratoconjunctivitis sicca (KCS), resulting from the inflammatory damage to the ocular surface tissues of cornea and conjunctiva. The diagnostic evaluation of KCS is a critical component of the classification criteria used by clinicians worldwide to confirm SS diagnosis. Therapeutic management of SS requires both topical and systemic treatments. Several mouse models of SS have contributed to our current understanding of immunopathologic mechanisms underlying the disease. This information also helps develop novel therapeutic interventions. Although these models address glandular aspects of SS pathology, their impact on ocular surface tissues is addressed only in a few models such as thrombospondin (TSP)-1 deficient, C57BL/6.NOD.Aec1Aec2, NOD.H2(b), NOD.Aire KO, and IL-2Rα (CD25) KO mice. While corneal and/or conjunctival damage is reported in most of these models, the characteristic SS specific autoantibodies are only reported in the TSP-1 deficient mouse model, which is also validated as a preclinical model. This review summarizes valuable insights provided by investigations on the ocular spectrum of the SS pathology in these models.